Topoisomerase III is required for accurate DNA replication and chromosome segregation in Schizosaccharomyces pombe - Oh, Misook (Oxford University Press, 2002)
The deletion of the top3(+) gene leads to defective nuclear division and lethality in Schizosaccharo myces pombe. This lethality is suppressed by concomitant loss of rqh1(+), the RecQ helicase. Despite extensive investigation, topoisomerase III function and its relationship with RecQ helicase remain poorly understood. We generated top3 temperature-sensitive (top3-ts) mutants and found these to be defective in nuclear division and cytokinesis and to be sensitive to DNA-damaging agents. A temperature shift of top3-ts cells to 37°C, or treatment with hydroxyurea at the permissive temperature, caused an increase in ‘cut’ (cell untimely torn) cells and elevated rates of minichromosome loss. The viability of top3-ts cells was decreased by a temperature shift during S-phase when compared with a similar treatment in other cell cycle stages. Furthermore, the top3-ts mutant was not sensitive to M-phase specific drugs. These results indicate that topoisomerase III may play an important role in DNA metabolism during DNA replication to ensure proper chromosome segregation. Our data are consistent with Top3 acting downstream of Rqh1 to process the toxic DNA structure produced by Rqh1.